Jute industry and imperatives for growth - Sur, Debanjan (Indian Farming, 2015)
The jute products, being biodegradable and hence eco-friendly, are poised for rapid growth in the world market provided we can encash this opportunity with judicious plan of actions both on jute agricultural and industrial fronts. Under this plan of actions, we should launch strategic campaign to promote jute products as eco-friendly materials; and we need to initiate vigorous activities for developing and commercializing a number of conventional and nonconventional jute-based products to offer as eco-friendly alternatives for synthetic products. Therefore, jute has a future provided we can judiciously engineer several marketable products by exploiting many of its unique characteristics. Jute has been found to be much suitable for producing many Technical Textiles with low-to-high value-addition.